2023
DOI: 10.1039/d2tb01389d
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-modified decellularized intestinal scaffolds loaded with adipose-derived stem cells promote intestinal regeneration

Abstract: Regeneration of gastrointestinal tissues remains a great challenge due to their unique microenvironment. Functional composite decellularized scaffolds have shown great potential in gastrointestinal repair and inducing gastrointestinal tissue-specific proliferation. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This study demonstrated that PDA coating significantly enhanced the roughness, hydrophilicity, and protein absorption capacity of the film, which promoted the adhesion and migration of MSCs onto biomaterial surfaces. In another investigation conducted by Wan et al [ 170 ], a PDA-mediated surface modification of decellularized intestinal scaffolds was combined with ADSC to promote intestinal wound healing. The PDA-coated scaffold effectively supported the growth and proliferation of ADSCs and enhanced their secretory activity for paracrine effects.…”
Section: Interaction Between Scaffolds and Mscsmentioning
confidence: 99%
“…This study demonstrated that PDA coating significantly enhanced the roughness, hydrophilicity, and protein absorption capacity of the film, which promoted the adhesion and migration of MSCs onto biomaterial surfaces. In another investigation conducted by Wan et al [ 170 ], a PDA-mediated surface modification of decellularized intestinal scaffolds was combined with ADSC to promote intestinal wound healing. The PDA-coated scaffold effectively supported the growth and proliferation of ADSCs and enhanced their secretory activity for paracrine effects.…”
Section: Interaction Between Scaffolds and Mscsmentioning
confidence: 99%
“…It has recently been shown that using the lentiviral system (vectors expressing Pdx1 and MafA/NeuroD1) it is possible to differentiate them into insulin-producing cells [ 108 ]. Using animal models, it has been shown that AD-MSC cells administered on appropriate decellularized intestinal scaffolds (polydopamine (PDA)-mediated surface modification) significantly accelerate intestinal regeneration, stimulate angiogenesis, and inhibit inflammation [ 109 ]. In another study, cells were transfected using liposomes with the plasmid Netrin-1.…”
Section: Bioengineered Ad-mscs In Regenerative Medicinementioning
confidence: 99%
“…It has been approved by the FDA, and the xenogenically derived SIS has been widely used in various tissue repair studies. Furthermore, in vivo has indicated that it is nonimmunogenic. Several studies have verified that SIS can provide a good microenvironment to facilitate the proliferation, attachment, and osteogenic differentiation of fibroblast bone, osteoblasts, and marrow mesenchymal stem cells. , In our previous study, SIS was applied to modify commercially available PMMA cement to optimize the biological performance and in vivo repair effect of the basic material . Though PMMA with 20 or 40% SIS powder showed excellent bioactivity to enhance the new bone formation, the compressive strength of the constructs was hard to meet the requirement of clinical application (ISO5833), which was essential for clinical application.…”
Section: Introductionmentioning
confidence: 99%